2017
DOI: 10.1038/s41598-017-08936-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Encoding of Self and Others’ Head Rotation in the Macaque Dorsal Prefrontal Cortex

Abstract: Following gaze is a crucial skill, in primates, for understanding where and at what others are looking, and often requires head rotation. The neural basis underlying head rotation are deemed to overlap with the parieto-frontal attention/gaze-shift network. Here, we show that a set of neurons in monkey’s Brodmann area 9/46dr (BA 9/46dr), which is involved in orienting processes and joint attention, becomes active during self head rotation and that the activity of these neurons cannot be accounted for by saccade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Significantly, we have been able to directly match our neurophysiological findings of a tuning of pAIP neurons to self and other’s observed actions with the neuro-anatomical evidence, obtained in the same animals, of 3 rostral-to-caudally increasing connectivity gradients. Compared with the intermediate and rostral levels of AIP, pAIP displays stronger connections with 1) a set of visual areas of the ventral stream that convey information about object features ( Sary et al 1993 ; Logothetis et al 1995 ; Saleem and Tanaka 1996 ; Koteles et al 2008 ; Hong et al 2016 ) and observed actions ( Perrett et al 1989 ; Nelissen et al 2011 ), in particular the dynamic body shape changes defining the action ( Vangeneugden et al 2009 ), 2) prefrontal cortical areas, including visually recipients areas 12r and 46 v ( Borra et al 2011 ; Gerbella et al 2013 ), involved in manual action planning ( Bruni et al 2015 ; Simone et al 2015 ) and observation ( Raos and Savaki 2017 ; Simone et al 2017 ; Fiave et al 2018 ), and 3) oculomotor regions, including area LIP, which may drive spatial attention processes aimed at proactively capturing goals and targets of others’ observed actions ( Flanagan and Johansson 2003 ; Falck-Ytter et al 2006 ; Elsner et al 2013 ; Maranesi et al 2013 ; Lanzilotto et al 2017 ). The specificity of this anatomofunctional association is underscored by the absence of a gradient in the connections with dorsovisual and skeletomotor related areas, as well as a reversed caudal-to-rostral incremental gradient for the connections with a large set of mainly parietal somatosensory regions, consistent with previous studies ( Lewis and Van Essen 2000 ; Borra et al 2008 ; Baumann et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, we have been able to directly match our neurophysiological findings of a tuning of pAIP neurons to self and other’s observed actions with the neuro-anatomical evidence, obtained in the same animals, of 3 rostral-to-caudally increasing connectivity gradients. Compared with the intermediate and rostral levels of AIP, pAIP displays stronger connections with 1) a set of visual areas of the ventral stream that convey information about object features ( Sary et al 1993 ; Logothetis et al 1995 ; Saleem and Tanaka 1996 ; Koteles et al 2008 ; Hong et al 2016 ) and observed actions ( Perrett et al 1989 ; Nelissen et al 2011 ), in particular the dynamic body shape changes defining the action ( Vangeneugden et al 2009 ), 2) prefrontal cortical areas, including visually recipients areas 12r and 46 v ( Borra et al 2011 ; Gerbella et al 2013 ), involved in manual action planning ( Bruni et al 2015 ; Simone et al 2015 ) and observation ( Raos and Savaki 2017 ; Simone et al 2017 ; Fiave et al 2018 ), and 3) oculomotor regions, including area LIP, which may drive spatial attention processes aimed at proactively capturing goals and targets of others’ observed actions ( Flanagan and Johansson 2003 ; Falck-Ytter et al 2006 ; Elsner et al 2013 ; Maranesi et al 2013 ; Lanzilotto et al 2017 ). The specificity of this anatomofunctional association is underscored by the absence of a gradient in the connections with dorsovisual and skeletomotor related areas, as well as a reversed caudal-to-rostral incremental gradient for the connections with a large set of mainly parietal somatosensory regions, consistent with previous studies ( Lewis and Van Essen 2000 ; Borra et al 2008 ; Baumann et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it is possible that such a mechanism aided infants in matching the congruent adult’s gaze shift to their own. Although typically associated with the encoding of manual actions or facial gestures ( di Pellegrino et al, 1992 ; Ferrari et al, 2003 ), mirror-like neurons for attention orienting and head rotation have been found in macaque monkeys ( Lanzilotto et al, 2017 ; Shepherd et al, 2009 ), and observed gaze direction modulates the activity of premotor mirror neurons selective for grasping ( Coude et al, 2016 ). Furthermore, mu ERD has been observed in adults during both RJA and IJA ( Lachat et al, 2012 ), suggesting that JA may involve a mechanism of attention mirroring ( Lachat et al, 2012 ; Shepherd et al, 2009 ; Triesch et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Action execution and observation recruit the same neural substrates in a wide set of brain regions in both human 1 , 2 , 3 and nonhuman primates. 4 , 5 , 6 Indeed, after the discovery of mirror neurons, a class of cells in the premotor area F5 of the macaque that become active during both the execution and observation of actions, 7 , 8 similar neuronal properties have been found in a larger network of anatomically connected brain regions, 9 , 10 , 11 which form the so-called action observation network (AON). The ventral premotor area F5 is thought to be the core of the AON and is certainly the most widely studied region.…”
Section: Introductionmentioning
confidence: 99%